﻿Patient satisfaction with clinical pharmacy services and the affecting factors: a literature review - Yuliandani Yuliandani; Sofa Dewi Alfian; Irma Melyani Puspitasari (Pensoft Publishers, 2022)
Service quality is measured to assess the consistency of medical services provided to fulfill patient expectations. This article provides an overview of patient satisfaction with clinical pharmacy services and the influencing factors. A literature search from MEDLINE and EBSCO databases was performed with the keywords "patient satisfaction", "pharmacy service", "hospital pharmacy service", and "clinical pharmacy service". The inclusion criteria for articles are original articles, full papers, articles in English, and published in 2011-2021. A total of 25 articles from 1,118 articles discussed patient satisfaction with clinical pharmacy services such as counseling, drug therapy monitoring, patient support programs, and pharmaceutical care. Generally, patients are satisfied with clinical pharmacy services such as counseling, drug therapy monitoring, patient support programs, and pharmaceutical care. The most influencing factors with clinical pharmacy services are the quality, convenience, ease of information, and confidence in pharmacist competence. Pharmacists should equip themselves with the appropriate knowledge and competencies in clinical pharmacy services for benefits their patients.